CHARACTERISTICS OF INSURANCE PROTECTION IN INCREASE OF PEASANTS AND FARMERS' INCOME (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article discusses the issues of increasing farmers' incomes through the introduction of insurance with the intensive development of agriculture on a scientific basis, based on the priorities of the development strategy of New Uzbekistan. Furthermore, recommendations of increasing the farmer`s income in the agro-industrial complex and their insurance protection are given.